Haptic contagion - Komel, Mirt (Filozofski vestnik, 2023)
During the pandemic there were many ways of handling the contagious SARS-CoV-2 virus, most of them in haptic terms, or in terms of touch: masks, hand disinfection, social distancing, quarantines, (self)isolations. Touch thus became not only the privileged object of the new bio-politics, striving to preserve life at all costs, but also what was lost during the pandemic. To be sure, a loss of something we never had that even the vaccine, which promised a return to normal, but actually paved the way for a “brave new post-pandemic world,” could not rehabilitate. In short, one of the elements that radically changed with and in the (post-)pandemic world is precisely the elusive object of touch, which we propose to conceptually grasp through the coinage of the concept of its “mateReal hapticity.”
Keywords: haptic studies; idealism; Idealizem (filozofija); materialism; Materializem; Psihoanaliza; psychoanalysis